2018
DOI: 10.1038/s41598-018-32253-0
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale mass wasting on small volcanic islands revealed by the study of Flores Island (Azores)

Abstract: Small intra-plate volcanic islands (total height above seafloor <2500 m) have been considered gravitationally stable. Topographic, stratigraphic, structural and new K/Ar data show that the small island of Flores (Azores) is strongly asymmetric and made up of nested volcanic successions. Along the northwestern coastline, ca. 1.2 Ma lava flows are in lateral contact with a younger volcanic unit (ca. 0.7 Ma), reflecting the existence of a steep lateral discontinuity. From the general dip of the lava flows, their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 65 publications
1
18
0
1
Order By: Relevance
“…In this regard, geochronological data is used to constrain the age of the different volcanic complexes, the age of the inferred large-scale mass wasting (LSMW), and the age of the different fossil deposits. Third, it is a very small island, therefore seemingly not prone to LSMW (Mitchell, 2003;Hildenbrand et al, 2018), which is in apparent contradiction with the LSMW inferred in Santa Maria.…”
Section: /) (B) -mentioning
confidence: 61%
See 1 more Smart Citation
“…In this regard, geochronological data is used to constrain the age of the different volcanic complexes, the age of the inferred large-scale mass wasting (LSMW), and the age of the different fossil deposits. Third, it is a very small island, therefore seemingly not prone to LSMW (Mitchell, 2003;Hildenbrand et al, 2018), which is in apparent contradiction with the LSMW inferred in Santa Maria.…”
Section: /) (B) -mentioning
confidence: 61%
“…Despite the small size of the Azorean islands, several LSMW events have been described recently (Hildenbrand et al, 2012a;Marques et al, 2013b;Sibrant et al, 2014Sibrant et al, , 2015aSibrant et al, , b, 2016Costa et al, 2014Costa et al, , 2015Marques et al, 2018;Hildenbrand et al, 2018). Exceptions in the eastern Azores are the islands of Faial (Hildenbrand et al, 2012b;Marques et al, 2014b;Trippanera et al, 2014) and Terceira Quartau et al, 2014), where LSMW has not been described (Mitchell, 2003;Casalbore et al, 2015;Quartau et al, 2012Quartau et al, , 2015.…”
Section: Lsmw Eventsmentioning
confidence: 98%
“…The samples were dated in Laboratory GEOPS (Univ. Paris-Sud, Orsay, France) with the unspiked K-Ar Cassignol-Gillot technique Gillot & Cornette, 1986), which allows the precise determination of small amounts of radiogenic argon ( 40 Ar*) and is particularly appropriate to date young volcanic rocks, including late quaternary low-K basalts and andesites (e.g., Bablon et al, 2018Bablon et al, , 2019Boulesteix et al, 2012Boulesteix et al, , 2013Costa et al, 2014Costa et al, , 2015Germa et al, 2010Germa et al, , 2011Hildenbrand et al, 2003Hildenbrand et al, , 2004Hildenbrand et al, , 2008Hildenbrand et al, , 2012Hildenbrand et al, , 2014Hildenbrand et al, , 2018Marques et al, 2015Marques et al, , 2018Quidelleur et al, 2008;Ricci et al, 2015Ricci et al, , 2017Ricci et al, , 2018Salvany et al, 2012;Sibrant et al, 2014;Sibrant, Hildenbrand, Marques, Weiss, et al, 2015;Silva et al, 2012Silva et al, , 2018. The technique has even been extended to the last millennium with an uncertainty of only a few centuries in the case of high-K lavas (Quidelleur et al, 2001).…”
Section: Analytical Techniques-k-ar Dating On Fresh Separated Groundmassmentioning
confidence: 99%
“…We used the decay constants and isotopic ratios of Steiger and Jäger (1977). The uncertainty on each age determination was obtained from the quadratic sum of all three independent sources of uncertainty involved in the calculation: (1) relative uncertainty on K-content determination, (2) relative uncertainty on calibration of the 40 Ar signal, and (3) relative uncertainty on the correction of the atmospheric contamination (full description in Hildenbrand et al, 2018).…”
Section: Geochronologymentioning
confidence: 99%
“…During the last two decades, numerous studies on the Azores archipelago brought new information on the timing of volcanism at both local and regional scales (e.g., Calvert et al, 2006;Costa et al, 2014;Sibrant et al, 2015;Hildenbrand et al, 2018;Marques et al, 2018). Johnson et al (1998) and Sibrant et al (2015) identified lava flow sequences in São Miguel island with ages close to the M-B reversal.…”
Section: Introductionmentioning
confidence: 99%